YOUNG TYPE INEQUALITIES FOR MATRICES - Peng, Yang (Italian Journal of Pure and Applied Mathematics, 2014)
In this note, we present a refinement of an inequality due to Hirzallah and Kittaneh [Linear Algebra Appl., 308 (2000), 77-84]. Meanwhile, we also obtain an improvement of a result shown by Kittaneh and Manasrah [Linear Multilinear Algebra, 59 (2011), 1031-1037].